Islamic Economics Ethics Perspective on Economic Development in the Time of Coronavirus Disease (Covid-19) - Rahmad Hakim; Muslikhati Muslikhati; Fitrian Aprilianto (Falah: Jurnal Ekonomi Syariah, 2020)
This study aims to provide an in-depth analysis of Islamic economics ethics on economic development in the time of coronavirus disease (Covid-19). This research was qualitative, using documentation techniques in data collection. The data analyzed using descriptive-qualitative technique. The conclusion of this study found that Islamic economic ethics in the economic development emphasizes on the role of the invidual (society) and institutions (government) in an active effort to manage the spread of coronavirus disease (Covid-19) by avoid an excessive buying, consume the halal and thayyib food, increase the alms giving activites and also the enforcement of fiscal and monetary policy.